2004
DOI: 10.1002/jcp.20090
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin induces mitotic catastrophe and subsequent apoptosis in human glioma cells

Abstract: Geldanamycin (GA) binds to heat shock protein 90 (Hsp90) and interferes with its function which is to protect various cellular proteins involved in signaling, growth control, and survival from ubiquitination and subsequent degradation by the proteasome. Recently, we demonstrated that GA inhibited migration of glioma cells in vitro associated with downregulation of hypoxia-inducible factor (HIF-1 alpha) and phosphorylation of focal adhesion kinase (FAK) (Zagzag et al., 2003, J Cell Physiol 196:394-402). Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 42 publications
8
37
1
Order By: Relevance
“…This G 2 /M arrest was sustained in synchronized U87 cells (Figure 1e). It has been shown that GA can induce mitotic catastrophe and apoptosis in T98 cells (Nomura et al, 2004). We have confirmed these data but we were able to observe accumulation of mitotic cells only in A172 and T98 cells (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…This G 2 /M arrest was sustained in synchronized U87 cells (Figure 1e). It has been shown that GA can induce mitotic catastrophe and apoptosis in T98 cells (Nomura et al, 2004). We have confirmed these data but we were able to observe accumulation of mitotic cells only in A172 and T98 cells (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…However, HSP90 inhibitors causing disruption or protein defects at the centrosome may be an additional mechanism causing HSP90 inhibitor-induced mitotic arrest and cell death. Similar to arsenite, the HSP90 inhibitor geldanamycin causes cell death through mitotic catastrophe in human glioma cells (Nomura et al, 2004). We also found that the HSP90 inhibitor 17-DMAG produced a mitotic arrest and induction of abnormal centrosome number ( Figure 7A and B).…”
Section: Discussionsupporting
confidence: 53%
“…Beyond a drug concentration of 100 nM, cell death seems solely dependent on the number of cells entering mitosis at a certain time. Recent findings by Nomura et al (32) suggest a phase-specific effect on glioma cells with S-phase cells being most sensitive, which points toward similar mechanisms as observed in our experiments. However, LSC provides no exact measure for cell death, since floating and dead cells might be washed away during the slide preparation.…”
Section: Discussionsupporting
confidence: 91%
“…human cervical carcinoma cells could be sensitized to radiation (37) and human breast cancer cells could be sensitized to Taxol (38). Cell cycle arrest either in G 1 -or G 2 =M-phase has been observed upon inhibition of Hsp90 and was suspected to depend on the presence or absence of the Rb gene product (32,36,39). The exact mechanism by which geldanamycin compromises the cell cycle is still a matter of controversy, and de Carcer recently reported results that suggest a major role of Hsp90 in controlling the metaphase-anaphase transition of HeLa cells through Polo-like kinase1 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation